The Effect Of Earnings Growth, Financial Ratios And Dividends On Stock Prices In Manufacturing Companies Listed On The LQ45 Index For The Period 2020 – 2022 - Nelya Arofatin; Salsabila Maulidya Supriadi Bahrim; Viona Eka Putri Mardiono; Maria Yovita R. Pandin (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study is to see the effect of profit growth, financial indicators and dividends on the share price of the manufacturing industry listed on the LQ45 index for the 2020-2022 period. This research uses a quantitative approach and uses the Structural Equation Modeling-Partial Least Squares (SEM-PLS) test tool. The data in this study were obtained from the financial statements of public companies in the manufacturing industry listed on the LQ45 index. Independent variables include earnings growth rate, return on assets (ROA), return on equity (ROE), price to earning ratio (PER), price to book ratio (PBV), and dividends paid by the company. Research shows that financial ratios which include ROA, ROE, PER, and PBV variables have a positive and significant influence on the stock price of a company, besides that although earnings growth has a positive impact on stock prices but is not significant on stock prices, the growth varies greatly, as well as dividends.This helps investors, financial managers, and business decision makers to understand the things that affect the stock price of manufacturing companies in the LQ45 index. If a company wants to maintain or increase its share value in a competitive market, it should consider its earnings history, financial metrics, and dividend policy.